Consensus Building on the Content of a Pediatric Pain Educational Program for Healthcare Professionals in a Low‐Resource Setting: A Modified e‐Delphi Study - Kusi Amponsah, Abigail; Badengo, Daniel Ba‐Eebu; Hammond, Charles Kumi; Bam, Victoria; Kyei‐Dompim, Joana; Wilson, Dorothy; Armah, Jerry; Oduro, Evans; Nawagi, Faith; Mukherjee, Snigdha; Axelin, Anna (Wiley, 2026)
Healthcare professionals (HCPs) play a key role in improving pain outcomes in hospitalized children. Knowledge gaps can significantly hinder the ability of HCPs to provide optimal pain care. Developing targeted educational interventions to address these gaps requires a clear understanding of priority areas for training on essential pain-related topics. Against this background, this study aimed to establish consensus on topics for a pediatric pain educational program (PPEP) for continuing professional education among HCPs. A two-stage modified e-Delphi study was conducted among experts in pediatric care, health education, and pain research. The researchers developed 35 topics by reviewing the Core Content of the Pediatric Pain PRN Curriculum. In the first and second rounds, experts rated the topics and suggested additional topics. Ratings were done on a four-point Likert scale with options ranging from 1 (not important at all) to 4 (very important). The outcomes from both rounds were analyzed based on the level of consensus. Consensus on a topic was set at a threshold of ≥ 70. A response rate of 88% (n = 22/25) and 100% (n = 22/22) was achieved for the first and second rounds, respectively. Experts rated 35 topics and 5 topics (the topic that failed to achieve consensus in the first round and four new ones generated from expert comments) in the first and second rounds, respectively. In the first round, experts agreed on 34 of the 35 topics (72.7%–90.9%) while all five topics achieved consensus (90.9%–100%) in the second round. Thus, 39 topics under the domains of pain theories, pediatric chronic pain, pain assessment, opioid risk evaluation and mitigation strategies (REMS), biobehavioural strategies, procedural pain, acute pain management and reorientation were agreed on for inclusion in the PPEP. A high level of consensus was achieved among a multidisciplinary panel of experts on the content of the PPEP. This can serve as a valuable resource for interprofessional pain continuing education in low-resource settings. The topics can also be integrated into curricula for preregistration healthcare professionals in such settings.